Determinants of uncontrolled allergic rhinitis in Kinshasa hospitals - Kakobo, Patricia K.; Kalala, Hilaire K.; Kelekele, Joseph K.; Mutombo, Paulin B.; Nyembue, Dieudonné T.; Hellings, Peter W.; Kayembe, Jean-Marie N. (Frontiers in Allergy, 2023)
Objective To identify the determinants of uncontrolled allergic rhinitis (UCAR) in a hospital setting in Kinshasa, Democratic Republic of Congo. Methods Hospital-based cross-sectional study of 153 patients with allergic rhinitis (AR). The diagnosis of AR was based on clinical grounds according to the Allergic Rhinitis and its Impact on Asthma (ARIA) criteria. Categorization into controlled AR (CAR) and UCAR was based on the visual analog scale (VAS with cut off point of 5). Binary logistic regression was used to identify factors associated with UCAR. Results Patients with UCAR (60.1%) proportionally outnumbered those with CAR (39.9%). There were significantly more patients younger than 30 years of age among patients with UCAR. Factors significantly associated with UCAR were age below 30 years (OR = 3.31; 95% CI: 1.49–7.36; p = 0.003), low serum vitamin D level (OR = 3.86; 95% CI: 1.72–8.68; p = 0.001), persistent form (OR = 3.11; 95% CI: 1.39–6.98; p = 0.006) and moderate to severe form of AR (OR = 4.31; 95% CI: 1.77–10.49; p = 0.001). Conclusions Factors associated with UCAR in this study population were younger age less than 30 years, low vitamin D level, and persistent as well as moderate to severe AR. Further studies are needed to elucidate the underlying mechanisms favoring the occurrence of these factors.